“This patient is not appropriate”: Perspectives of physiotherapy students and clinical educators on exposing students to patients with complex needs during clinical practice placements - McGivern, Elaine; Mandrusiak, Allison; Rahmann, Ann; Forbes, Roma (Physiotherapy theory and practice, 2025)
Clinical practice placements play an important role in preparing students for challenging areas of clinical practice. Little is known about student learning needs for working with patients with complex needs during clinical practice placements, and clinical educator decision-making that underpins this exposure. To explore the perspectives of physiotherapy students and clinical educators on exposing students to working with and learning from patients with complex needs during clinical practice placements across Queensland and New South Wales, Australia. Six semi-structured focus groups with pre-registration physiotherapy students undertaking clinical practice placements ( = 19) and semi-structured one-on-one interviews with clinical educators ( = 20). Data were analyzed using reflexive thematic analysis. Four overarching themes were generated following analysis: 1) Complexity is challenging; 2) Tension between student exposure and patient care; 3) Variance in expectations; and 4) Readiness for complexity. Physiotherapy students and clinical educators recognize the challenges and importance of exposure to patients with complex needs. Student learning experiences are influenced by clinical educator decision-making, which is often unclear, leading to varying opportunities. This study highlights the need for enhanced support from clinical educators to prepare students for working with patients with complex needs.